Oxidation kinetics in pearlite: The defining role of interface crystallography. (15th July 2018) - Mehtani, H.K.; Khan, M.I.; Durgaprasad, A.; Deb, S.K.; Parida, S.; Prasad, M.J.N.V.; Samajdar, I.
Abstract: Five different pearlitic steel wires were produced through controlled thermomechanical processing. These wires had significant ( 2 times) differences in the pearlite alignment and also exhibited nearly one order of magnitude difference in the oxidation kinetics. Though the nature of the oxide films was not remarkably different, the stresses in the majority hematite phase scaled with the experimentally measured oxidation rates. Careful correlation between substrate microstructure and oxide stresses established that the stresses were highest at the ferrite-cementite interface. And the interface crystallography, in case of the coarse pearlite, determined such stresses and the oxidation kinetics. Graphical abstract: Unlabelled Image